High-stability monatomic catalyst, synthesis method and application of high-stability monatomic catalyst in preparation of methanol through catalytic hydrogenation of carbon dioxide

The coordination structure between precious metal atoms and oxide support is optimized by solvent-free mechanochemical synthesis method, and a high-stable single-atom catalyst was prepared, which solved the problems of poor stability and low selectivity of the catalyst in the methanol reaction of CO2 catalytic hydrogenation, and achieved efficient CO2 conversion and methanol selectivity.

CN119657127AActive Publication Date: 2025-03-21XI AN JIAOTONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411903529.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-21
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing single-atom catalysts have poor stability in the hydrogenation of CO2 to methanol reaction, are prone to agglomeration and inactivation, and have uneven product distribution and low selectivity of methanol.

Method used

Through solvent-free mechanochemical synthesis, the noble metal precursor and the transition metal precursor are ball milled to optimize the coordination structure and strong interaction between precious metal atoms and oxide support. Through the steps of fast calcination of low temperature and slow calcination of high temperature, a high-stable single-atom catalyst is prepared.

Benefits of technology

The high conversion efficiency of CO2 and the high selectivity of methanol are achieved, and the catalyst operates stably for more than 200 hours, solving the problems of poor stability and low selectivity of traditional catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657127A_ABST
    Figure CN119657127A_ABST
Patent Text Reader

Abstract

The invention discloses a high-stability monatomic catalyst, a synthesis method and application of the high-stability monatomic catalyst in preparation of methanol through catalytic hydrogenation of carbon dioxide, acetylacetone metal salt A and acetylacetone metal salt B are subjected to machine milling and then roasted twice, and the high-stability monatomic catalyst is obtained; the acetylacetone salt A is platinum acetylacetonate, palladium acetylacetonate, rhodium acetylacetonate or ruthenium acetylacetonate; the acetylacetone metal salt B is manganese acetylacetonate, iron acetylacetonate, nickel acetylacetonate, chromium acetylacetonate, lanthanum acetylacetonate, cerium acetylacetonate, cobalt acetylacetonate, copper acetylacetonate, zinc acetylacetonate, zirconium acetylacetonate, indium acetylacetonate, tin acetylacetonate or molybdenum acetylacetonate. The combination mode of an active interface formed by precious metal single atoms and a metal oxide carrier is adjusted through machine milling, so that an energy barrier for adsorbing and activating CO2 molecules into formate is adjusted and controlled; and the lattice charge balance driving force of the metal oxide carrier enables active hydrogen dissociated from the metal active site to continuously overflow to the surface of the active center at a lower energy barrier, so that the selectivity of the product methanol is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of air pollution control, and particularly relates to a highly stable single-atom catalyst and a synthesis method and application thereof in catalytic hydrogenation of carbon dioxide to produce methanol. Technical Background

[0002] With the increasing severity of global climate change and energy crisis, converting excess CO2 in the atmosphere into usable carbon resources is the only way for mankind to achieve carbon neutrality and practice sustainable development. Among the many CO2 resource utilization technologies, thermodynamic CO2 hydrogenation technology has been widely studied and paid attention to due to its advantages such as controllable conditions and easy operation. Converting CO2 into high-energy-density fuels and high-value-added carbon products through hydrogenation reduction technology is one of the important ways to reduce the CO2 concentration in the atmosphere, store intermittent renewable energy, and achieve carbon neutrality. Converting the captured pre-concentrated CO2 into high-value-added products such as methanol and dimethyl ether through a catalytic hydrogenation reduction process can not only effectively control the greenhouse effect caused by excessive CO2 emissions, but also help alleviate the energy crisis caused by the shortage of fossil energy.

[0003] The C=O bond of CO2 is activated usually by transferring electrons from the metal d-bonding orbital to the CO2 antibonding orbital to form CO2 δ- Therefore, it is necessary to construct active centers with high charge density to improve the low-temperature activation efficiency of molecules. Single-atom catalysts have been widely used in heterogeneous catalytic reactions because they have the highest metal atom utilization efficiency. The high atomic utilization rate and unique electronic-geometric structure of single-atom catalysts enable them to exhibit excellent catalytic performance in a series of important reactions. However, common single-atom catalysts have poor stability and are easily agglomerated and deactivated in high-temperature and high-pressure reducing atmospheres. Therefore, they cannot be used in the reaction of CO2 catalytic hydrogenation to methanol. In addition, due to the randomness of the coordination structure of traditional single-atom catalysts, the products after CO2 hydrogenation are unevenly distributed, and the selectivity of the high-value product methanol is low. Summary of the invention

[0004] In order to overcome the technical problem of low methanol selectivity in the reaction of catalytic hydrogenation of CO2 to methanol in the prior art, the purpose of the present invention is to provide a highly stable single-atom catalyst and a synthesis method and its application in catalytic hydrogenation of carbon dioxide to methanol.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] A method for synthesizing a highly stable single-atom catalyst comprises the following steps:

[0007] Acetylacetonate metal salt A and acetylacetonate metal salt B are mechanically ground and then calcined twice to obtain a highly stable single-atom catalyst;

[0008] Acetylacetonate A is platinum acetylacetonate, palladium acetylacetonate, rhodium acetylacetonate or ruthenium acetylacetonate;

[0009] The acetylacetonate metal salt B is manganese acetylacetonate, iron acetylacetonate, nickel acetylacetonate, chromium acetylacetonate, lanthanum acetylacetonate, cerium acetylacetonate, cobalt acetylacetonate, copper acetylacetonate, zinc acetylacetonate, zirconium acetylacetonate, indium acetylacetonate, tin acetylacetonate or molybdenum acetylacetonate.

[0010] Furthermore, the molar ratio of the acetylacetonate metal salt A to the acetylacetonate metal salt B is 1:10-50.

[0011] Furthermore, the ball milling speed is 2000-4000 rpm, and the ball milling time is 5-12 h.

[0012] Furthermore, the sample after mechanical ball milling is dried at a temperature of 60-80° C. and a drying time of 6-12 h.

[0013] Furthermore, the primary calcination temperature is 300-400°C, and the calcination time is 3-4h.

[0014] Further, at 3-5℃·min -1 The heating rate is increased to 300-400°C.

[0015] Furthermore, the secondary calcination treatment temperature is 500-550° C., and the calcination time is 3-4 hours.

[0016] Further, at 1-2℃·min -1 The heating rate is increased to 500-550°C.

[0017] A highly stable single-atom catalyst, in which noble metal active sites are atomically dispersed on the surface of a metal oxide carrier.

[0018] Application of a highly stable single-atom catalyst in the heterogeneous catalytic hydrogenation of CO2 to methanol.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The content of the present invention is based on optimizing the coordination structure between noble metal atoms and oxide carriers and enhancing their strong interaction. First, the noble metal precursor and the transition metal precursor are ball-milled and mixed by a solvent-free mechanochemical synthesis method. In this step, a strong coordination force is generated between different metal precursors through mechanical ball milling, thereby enhancing the strong interaction ability between the noble metal atoms and the carrier. Subsequently, during the low-temperature rapid calcination process, the stable and rapid dissociation of the organic ligands in the metal salt precursor is promoted; then, through solvent thermal washing, the noble metal ions with weak binding force between the catalyst surface and the metal oxide carrier are removed, so that the remaining noble metal atom active centers have a strong interaction with the carrier. Finally, these noble metal atoms are firmly anchored on the surface of the metal oxide carrier through high-temperature slow baking, thereby preparing a highly stable single-atom catalyst.

[0021] In the present invention, the bonding mode of the active interface formed by the noble metal single atom and the metal oxide carrier is adjusted by optimizing the mechanical ball milling time, thereby regulating the energy barrier of CO2 molecule adsorption activation into formate. At the same time, the "lattice charge balance" driving force of the metal oxide carrier enables the active hydrogen (H*) dissociated from the metal active site to continuously overflow to the surface of the active center with a lower energy barrier, thereby inhibiting the generation of CO and CH4 products in the heterogeneous catalytic hydrogenation process of CO2, and greatly improving the selectivity of the product methanol. The catalyst prepared by the present invention has a high selectivity to methanol at 280°C, 3Mpa, and a space velocity of 12,000h -1 , under the conditions of gas ratio of 70% H2:25% CO2:5% N2, the CO2 conversion efficiency is higher than 8%, and the selectivity of product methanol is greater than 80%, and it can run stably for more than 200 hours. The present invention has simple process, environmental friendliness, large preparation volume, good scalability, and adjustable precious metal loading. It is expected to solve the technical bottleneck of poor stability and easy sintering of traditional precious metal-based catalysts in CO2 catalytic hydrogenation reaction, and promote theoretical innovation and technological progress in the field of CO2 resource utilization and renewable energy development. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 These are spherical aberration electron microscope (STEM) images of the highly stable Pd1-ZnO single-atom catalyst in the present invention, wherein (a) is before the catalytic reaction and (b) is after the catalytic reaction.

[0023] Figure 2 These are spherical aberration electron microscope (STEM) images of the highly stable Pd1-In2O3 single-atom catalyst in the present invention, wherein (a) is before the catalytic reaction and (b) is after the catalytic reaction.

[0024] Figure 3 These are spherical aberration electron microscope (STEM) images of the highly stable Rh1-ZnO single-atom catalyst in the present invention, wherein (a) is before the catalytic reaction and (b) is after the catalytic reaction.

[0025] Figure 4 These are the spherical aberration electron microscope STEM image and EDS-mapping image of the highly stable Rh1-In2O3 single-atom catalyst in the present invention, wherein (a) is the spherical aberration electron microscope STEM image, and (b) is the EDS-mapping image.

[0026] Figure 5 These are the activity test results of the highly stable single-atom catalysts of Examples 1-4 of the present invention. DETAILED DESCRIPTION

[0027] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.

[0028] The present invention designs and develops a highly stable single-atom catalytic material system with a simple preparation method and high universality to improve the catalytic stability and product selectivity of single-atom catalysts for CO2 hydrogenation. The present invention will provide a scientific basis and theoretical foundation for the design of high-performance materials for CO2 hydrogenation and the selection of product selectivity control methods, and has important application prospects in the fields of CO2 emission reduction control and high-value conversion.

[0029] The present invention discloses a method for synthesizing a highly stable single-atom catalyst. The method comprises the following steps: ball-milling and mixing a noble metal precursor and a transition metal precursor by a solvent-free mechanochemical synthesis method. In this step, mechanical ball milling is used to generate a strong coordination force between different metal precursors, thereby enhancing the strong interaction ability between the noble metal atoms and the carrier. Subsequently, during a low-temperature rapid calcination process, the stable and rapid dissociation of the organic ligands in the metal salt precursor is promoted. Subsequently, solvent thermal washing is used to remove the noble metal ions with weak binding force with the metal oxide carrier on the catalyst surface, so that the remaining noble metal atom active centers have a strong interaction with the carrier. Finally, the noble metal atoms are firmly anchored on the surface of the metal oxide carrier by high-temperature slow calcination, thereby preparing a highly stable single-atom catalyst.

[0030] In addition, by optimizing the mechanical ball milling time, the bonding mode of the active interface formed by the noble metal single atom and the metal oxide support is adjusted, thereby regulating the energy barrier for the adsorption and activation of CO2 molecules into formate. At the same time, the "lattice charge balance" driving force of the metal oxide support enables the active hydrogen (H*) dissociated from the metal active site to continuously overflow to the surface of the active center with a lower energy barrier, thereby inhibiting the formation of CO and CH4 products during the heterogeneous catalytic hydrogenation of CO2, and greatly improving the selectivity of the product methanol.

[0031] The synthesis method of the present invention specifically comprises the following steps:

[0032] (1) 0.0001 mol of acetylacetonate metal salt A (which may be one of acetylacetonate platinum, acetylacetonate palladium, acetylacetonate rhodium, and acetylacetonate ruthenium) and 0.001-0.005 mol of acetylacetonate metal salt B (which may be one of acetylacetonate manganese, acetylacetonate iron, acetylacetonate nickel, acetylacetonate chromium, acetylacetonate lanthanum, acetylacetonate cerium, acetylacetonate cobalt, acetylacetonate copper, acetylacetonate zinc, acetylacetonate zirconium, acetylacetonate indium, acetylacetonate tin, and acetylacetonate molybdenum) are ground evenly in a crucible and then placed in a ball mill cavity.

[0033] (2) The powder in step (1) is subjected to mechanical ball milling, the diameter of the agate beads used is 0.5-10 mm, the rotation speed of the mechanical ball mill is 2000-4000 rpm, and the ball milling time is 5-12 h.

[0034] (3) Dry the solid powder obtained in step (2) at 60-80°C for 6-12h.

[0035] (4) calcining the solid sample obtained in step (3) at 300-400°C in air atmosphere for 2-3h at a heating rate of 1-2.5°C·min -1 .

[0036] (5) The solid powder obtained in step (4) was dispersed in 30 mL of dimethyl sulfoxide and ultrasonically washed at 40-60° C. After centrifugation, the obtained sample was ultrasonically washed twice with 30-50 mL of ethanol-deionized water mixed solution (the volume ratio of ethanol to deionized water was 3:1).

[0037] (6) Dry the sample obtained in step (5) at 60-80°C for 6-12h.

[0038] (7) calcining the sample obtained in step (6) at 500-550°C in air atmosphere for 3-4h at a heating rate of 1-2°C·min -1 .

[0039] The highly stable single-atom catalyst prepared by the present invention can be used in the CO2 heterogeneous catalytic hydrogenation to methanol reaction. Specifically, at 280°C, 3Mpa, and a space velocity of 12,000h -1 Under the conditions of a gas volume ratio of 70% H2:25% CO2:5% N2, the CO2 conversion efficiency is higher than 8%, and the selectivity of the product methanol is greater than 80%. The efficiency of CO2 hydrogenation to methanol can be stably maintained for more than 100 hours, and can operate stably for more than 200 hours, with excellent stability and catalytic efficiency.

[0040] The following are specific embodiments.

[0041] Example 1 Preparation of Highly Stable Pd1-ZnO Single Atom Catalyst

[0042] Weigh 0.031g of palladium acetylacetonate and 2.63g of zinc acetylacetonate and mix them evenly in a mortar. Place the mixed metal salt precursor in the ball mill chamber and randomly mix it with agate beads of different sizes with a diameter of 0.5-10mm. The sample is mechanically ball milled for 10 hours at a speed of 3000rpm. Subsequently, the obtained solid powder is dried at 70℃ for 12h and then calcined at 300℃ in air atmosphere for 2h with a heating rate of 1℃·min -1 The obtained sample was dispersed in 30 mL of dimethyl sulfoxide and ultrasonically washed at 50°C. After centrifugation, the obtained sample was ultrasonically washed twice with 30 mL of ethanol-deionized water mixed solution. The obtained solid powder was dried at 70°C for 12 h and then calcined at 500°C in air atmosphere for 4 h with a heating rate of 2°C·min -1 , and finally a highly stable Pd1-ZnO catalyst was obtained.

[0043] See also Figure 1 In (a) and (b), Figure 1 From the spherical aberration electron microscope (STEM), it can be seen that the active components of the highly stable Pd1-ZnO single-atom catalyst maintain atomic-level dispersion before and after the reaction.

[0044] Example 2 Preparation of Highly Stable Pd1-In2O3 Single Atom Catalyst

[0045] Weigh 0.031g of acetylacetonate palladium and 4.12g of acetylacetonate indium and mix them evenly in a mortar. Place the mixed metal salt precursor in the ball mill chamber and randomly mix it with agate beads of different sizes with diameters of 0.5-10mm. The sample is mechanically ball milled for 10h at a speed of 3000rpm. Subsequently, the obtained solid powder is dried at 70℃ for 12h and then calcined at 300℃ in air atmosphere for 2h at a heating rate of 1℃·min -1 The obtained sample was dispersed in 30 mL of dimethyl sulfoxide and ultrasonically washed at 50°C. After centrifugation, the obtained sample was ultrasonically washed twice with 30 mL of ethanol-deionized water mixed solution. The obtained solid powder was dried at 70°C for 12 h and then calcined at 500°C in air atmosphere for 4 h with a heating rate of 2°C·min -1 , and finally a highly stable Pd1-In2O3 catalyst was obtained.

[0046] See also Figure 2 In (a) and (b), Figure 2From the spherical aberration electron microscope STEM, it can be seen that the active components of the highly stable Pd1-In2O3 single-atom catalyst maintain atomic-level dispersion before and after the reaction.

[0047] Example 3 Preparation of Highly Stable Rh1-ZnO Single Atom Catalyst

[0048] Weigh 0.040g of palladium acetylacetonate and 2.63g of zinc acetylacetonate and mix them evenly in a mortar. Place the mixed metal salt precursor in the ball mill chamber and randomly mix it with agate beads of different sizes with diameters of 0.5-10mm. The sample is mechanically ball milled for 10h at a speed of 3000rpm. Subsequently, the obtained solid powder is dried at 70℃ for 12h and then calcined at 300℃ in air atmosphere for 2h with a heating rate of 1℃·min -1 The obtained sample was dispersed in 30 mL of dimethyl sulfoxide and ultrasonically washed at 50°C. After centrifugation, the obtained sample was ultrasonically washed twice with 30 mL of ethanol-deionized water mixed solution. The obtained solid powder was dried at 70°C for 12 h and then calcined at 500°C in air atmosphere for 4 h with a heating rate of 2°C·min -1 , and finally a highly stable Rh1-ZnO catalyst was obtained.

[0049] See also Figure 3 In (a) and (b), Figure 3 From the spherical aberration electron microscopy (STEM), it can be seen that the active components of the highly stable Rh1-ZnO single-atom catalyst maintain atomic-level dispersion before and after the reaction.

[0050] Example 4 Preparation of Highly Stable Rh1-In2O3 Single Atom Catalyst

[0051] Weigh 0.040g of acetylacetonate palladium and 4.12g of acetylacetonate indium and mix them evenly in a mortar. Place the mixed metal salt precursor in the ball mill chamber and randomly mix it with agate beads of different sizes with a diameter of 0.5-10mm. The sample is mechanically ball milled for 10h at a speed of 3000rpm. Subsequently, the obtained solid powder is dried at 70℃ for 12h and then calcined at 300℃ in air atmosphere for 2h at a heating rate of 1℃·min -1 The obtained sample was dispersed in 30 mL of dimethyl sulfoxide and ultrasonically washed at 50°C. After centrifugation, the obtained sample was ultrasonically washed twice with 30 mL of ethanol-deionized water mixed solution. The obtained solid powder was dried at 70°C for 12 h and then calcined at 500°C in air atmosphere for 4 h with a heating rate of 2°C·min -1 , and finally a highly stable Rh1-In2O3 catalyst was obtained.

[0052] See also Figure 4In (a) and (b), Figure 4 The spherical aberration electron microscopy STEM and EDS-mapping images show that the active components of the highly stable Rh1-In2O3 single-atom catalyst maintain atomic-level dispersion before and after the reaction.

[0053] Example 5 Catalyst catalytic CO2 hydrogenation activity and stability test

[0054] The heterogeneous catalytic hydrogenation of CO2 was carried out in a fixed bed tubular reactor (total length 304.8 mm, inner diameter 9.1 mm). Before the activity test, the catalyst (150 mg) was first pretreated under H2 at 300 °C for 60 min. The mixed gas ratio was H2 / CO2 / N2 = 3 / 1 / 1 (N2 was used as the internal standard), and the gas flow rate was 30 mL min -1 The reaction was carried out at 200-280°C and 30 bar, and the product was analyzed online by gas chromatography (Clarus 580; PerkinElmer) equipped with TCD and flame ionization detector. The specific calculation formula of catalytic activity is as follows:

[0055]

[0056]

[0057]

[0058]

[0059] In the formula, CO2 conversion is the carbon dioxide concentration, n CO2,in is the input carbon dioxide molar amount, n CO2,out To output the molar amount of carbon dioxide, MeOH selectivity is the methanol selectivity, n MeOH,out is the molar amount of methanol output, n CO,out is the molar amount of carbon monoxide output, MeOH specific yield is the methanol yield, F CO2 is the partial pressure of CO2, M MeOH is the output mass of methanol, m cat is the mass of the catalyst, w m is the metal loading.

[0060] The stability test of the catalytic reaction was carried out under the following conditions: the catalyst mass was 150 mg, the mixed gas ratio was H2 / CO2 / N2=3 / 1 / 1 (N2 was used as the internal standard), and the gas flow rate was 30 mL min -1The stability test was carried out at 280 °C and 30 bar, and the products were analyzed online by gas chromatography (Clarus 580; PerkinElmer) equipped with TCD and flame ionization detector.

[0061] See also Figure 5 ,Depend on Figure 5 The activity test results show that the highly stable single-atom catalyst prepared by the present invention has a high activity at 280°C, 3Mpa, and a space velocity of 12,000h -1 Under the conditions of gas ratio of 70% H2:25% CO2:5% N2, the CO2 conversion efficiency is higher than 8%, and the selectivity of product methanol is greater than 80%.

[0062] Example 6

[0063] Weigh 0.0001 mol of acetylacetonate palladium and 0.005 mol of acetylacetonate zinc and mix them evenly in a mortar. Place the mixed metal salt precursor in the ball mill chamber and randomly mix it with agate beads of different sizes with a diameter of 0.5-10 mm. The sample is mechanically ball milled for 12 hours at a speed of 2000 rpm. Subsequently, the obtained solid powder is dried at 60°C for 12 hours and then calcined at 400°C in an air atmosphere for 2 hours at a heating rate of 2°C·min -1 The obtained sample was dispersed in 30 mL of dimethyl sulfoxide and ultrasonically washed at 40°C. After centrifugation, the obtained sample was ultrasonically washed twice with 40 mL of ethanol-deionized water mixed solution. The obtained solid powder was dried at 60°C for 12 h and then calcined at 520°C in air atmosphere for 3 h with a heating rate of 1°C·min -1 , and finally a highly stable single-atom catalyst was obtained.

[0064] Example 7

[0065] Weigh 0.0001 mol of acetylacetonate palladium and 0.001 mol of acetylacetonate zinc and mix them evenly in a mortar. Place the mixed metal salt precursor in the ball mill chamber and randomly mix it with agate beads of different sizes with diameters of 0.5-10 mm. The sample is mechanically ball milled for 8 hours at a speed of 2500 rpm. Subsequently, the obtained solid powder is dried at 65°C for 10 hours and then calcined at 350°C in an air atmosphere for 2.5 hours at a heating rate of 2.5°C·min -1 The obtained sample was dispersed in 30 mL of dimethyl sulfoxide and ultrasonically washed at 60°C. After centrifugation, the obtained sample was ultrasonically washed twice with 50 mL of ethanol-deionized water mixed solution. The obtained solid powder was dried at 70°C for 8 h and then calcined at 550°C in air atmosphere for 3 h with a heating rate of 2°C·min -1, and finally a highly stable single-atom catalyst was obtained.

[0066] Example 8

[0067] Weigh 0.0001 mol of acetylacetonate palladium and 0.003 mol of acetylacetonate zinc in a mortar and mix them evenly. Place the mixed metal salt precursor in a ball mill chamber and randomly mix it with agate beads of varying sizes with diameters of 0.5-10 mm. The sample is mechanically ball milled for 5 hours at a speed of 4000 rpm. Subsequently, the obtained solid powder is dried at 80°C for 68 hours and then calcined at 320°C in an air atmosphere for 3 hours at a heating rate of 1.5°C·min -1 The obtained sample was dispersed in 30 mL of dimethyl sulfoxide and ultrasonically washed at 50°C. After centrifugation, the obtained sample was ultrasonically washed twice with 30 mL of ethanol-deionized water mixed solution. The obtained solid powder was dried at 80°C for 6 h and then calcined at 500°C in air atmosphere for 4 h with a heating rate of 1.5°C·min -1 , and finally a highly stable single-atom catalyst was obtained.

[0068] Example 9

[0069] Same as Example 8, except that zinc acetylacetonate is replaced by manganese acetylacetonate.

[0070] Example 10

[0071] Same as Example 8, except that zinc acetylacetonate is replaced by ferric acetylacetonate.

[0072] Embodiment 11

[0073] Same as Example 8, except that zinc acetylacetonate is replaced by nickel acetylacetonate.

[0074] Example 12

[0075] Same as Example 8, except that zinc acetylacetonate is replaced by chromium acetylacetonate.

[0076] Embodiment 13

[0077] Same as Example 8, except that zinc acetylacetonate is replaced by lanthanum acetylacetonate.

[0078] Embodiment 14

[0079] Same as Example 8, except that zinc acetylacetonate is replaced by cerium acetylacetonate.

[0080] Embodiment 15

[0081] Same as Example 8, except that zinc acetylacetonate is replaced by cobalt acetylacetonate.

[0082] Example 16

[0083] Same as Example 8, except that zinc acetylacetonate is replaced by copper acetylacetonate.

[0084] Embodiment 17

[0085] Same as Example 8, except that zinc acetylacetonate is replaced by zirconium acetylacetonate.

[0086] Embodiment 18

[0087] Same as Example 8, except that zinc acetylacetonate is replaced by tin acetylacetonate.

[0088] Embodiment 19

[0089] Same as Example 8, except that zinc acetylacetonate is replaced by molybdenum acetylacetonate.

[0090] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.

[0091] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

Claims

1. A method for synthesizing a highly stable single-atom catalyst, characterized in that: The following steps are involved: Acetylacetonate metal salt A and acetylacetonate metal salt B are mechanically ground and then calcined twice to obtain a highly stable single-atom catalyst; Acetylacetonate A is platinum acetylacetonate, palladium acetylacetonate, rhodium acetylacetonate or ruthenium acetylacetonate; The acetylacetonate metal salt B is manganese acetylacetonate, iron acetylacetonate, nickel acetylacetonate, chromium acetylacetonate, lanthanum acetylacetonate, cerium acetylacetonate, cobalt acetylacetonate, copper acetylacetonate, zinc acetylacetonate, zirconium acetylacetonate, indium acetylacetonate, tin acetylacetonate or molybdenum acetylacetonate.

2. The method for synthesizing a highly stable single-atom catalyst according to claim 1, characterized in that: The molar ratio of the acetylacetonate metal salt A to the acetylacetonate metal salt B is 1:10-50.

3. The method for synthesizing a highly stable single-atom catalyst according to claim 1, characterized in that: The ball milling speed is 2000-4000rpm, and the ball milling time is 5-12h.

4. The method for synthesizing a highly stable single-atom catalyst according to claim 1, characterized in that: The sample after mechanical ball milling is dried at a temperature of 60-80°C and a drying time of 6-12h.

5. The method for synthesizing a highly stable single-atom catalyst according to claim 1, characterized in that: The primary calcination temperature is 300-400°C and the calcination time is 3-4h.

6. The method for synthesizing a highly stable single-atom catalyst according to claim 5, characterized in that: 3-5℃·min -1 The heating rate is increased to 300-400°C.

7. The method for synthesizing a highly stable single-atom catalyst according to claim 1, characterized in that: The secondary calcination treatment temperature is 500-550°C and the calcination time is 3-4h.

8. The method for synthesizing a highly stable single-atom catalyst according to claim 7, characterized in that: 1-2℃·min -1 The heating rate is increased to 500-550°C.

9. A highly stable single-atom catalyst prepared by the synthesis method according to any one of claims 1 to 8, characterized in that: The noble metal active sites in the catalyst are dispersed at the atomic level on the surface of the metal oxide support.

10. Use of a highly stable single-atom catalyst prepared by the synthesis method according to any one of claims 1 to 8 in the CO2 heterogeneous catalytic hydrogenation reaction to produce methanol.

Citation Information

Patent Citations

  • Macro preparation method for monoatomic catalyst

    CN108927155A

  • Monatomic catalyst and application thereof in carbon dioxide hydrogenation reaction

    CN111530458A

  • Monatomic Pt-doped indium oxide catalyst as well as preparation method and application thereof

    CN118179498A

  • Macro preparation method for monoatomic catalyst

    WO2020000627A1